Pemberian Dietilnitrosamin dan Karbontetraklorida Pada Gambaran Histologi Ginjal Tikus (Rattus Norvegicus) - Almas Dwi Khairana; Ricadonna Raissa; Wibi Riawan; Suharti Suharti; Hendra Susanto; Aulanni’am Aulanni’am (Sarana Ilmu Indonesia (salnesia), 2022)
Diethylnitrosamine (DEN) is a metabolic product of various foods and beverages in which there are preservatives in the form of nitrate and nitrite. Nitrosamines are found in various products such as alcoholic beverages, processed meats, cigarettes, and cosmetic products. DEN is toxic and carcinogenic to organs such as the liver, lungs, kidneys, skin, stomach, and blood. In addition to giving DEN compounds, there are also CCl4 compounds as tumor promoter agents known as genotoxic substances that can increase the risk of genetic errors and stimulate cells to become malignant neoplasms. Administration of DEN and CCl4 induction can damage various organs of the body, one of which is the kidney. In a healthy body, angiogenesis plays a role in wound healing and the formation of new tissue. However, angiogenesis also contributes to carcinogenesis or the uncontrolled growth of cancer cells, and is malignant when the body is contaminated with toxic substances. Therefore, to determine the effect of the administration of DEN and CCl4 observations were made using the immunohistochemical method, to see differences in the histology of the kidneys of experimental animals, the positive control group, and the negative control group based on the VEGF angiogenesis factor. From these results, there are significant differences. In the negative group, there was no necrosis and high-value VEGF expression, but in the positive group, there was necrosis and a decrease in the value of VEGF expression compared to the negative control group.